Exosomal zinc transporter ZIP4 promotes cancer growth and is a novel diagnostic biomarker for pancreatic cancer. Issue 9 (5th September 2018) - Jin, Haoyi; Liu, Peng; Wu, Yunhao; Meng, Xiangli; Wu, Mengwei; Han, Jiahong; Tan, Xiaodong
Abstract : Pancreatic cancer is one of the deadliest cancers with rapid disease progression. Further elucidation of its underlying molecular mechanisms and novel biomarkers for early detection is necessary. Exosomes are small extracellular vesicles that are released by multiple cell types acting as message carriers during intercellular communication and are promising biomarker candidates. However, the role of pancreatic cancer cell‐derived exosomes in cancer progression and the application of these vesicles as novel diagnostic biomarkers have not been fully studied. In this study, we found that PC‐1.0 (a highly malignant pancreatic cell line) cell‐derived exosomes could be taken up by and enhance PC‐1 (a moderately malignant pancreatic cell line) cell proliferation, migration and invasion abilities. We identified ZIP4 as the most upregulated exosomal protein in PC‐1.0 cells from our proteomic analysis. In vitro and in vivo (a subcutaneous BALB/c nude mouse model) studies showed that exosomal ZIP4 can significantly promote pancreatic cancer growth. Using clinical blood samples, we compared the diagnostic values of serum exosomal ZIP4 levels between malignant pancreatic cancer patients (n = 24) and benign pancreatic disease patients (n = 32, AUC = .89), and between biliary disease patients (n = 32, AUC = .8112) and healthy controls (n = 46, AUC = .8931). In conclusion, exosomal ZIP4 promotes cancer growth and is a novel diagnostic biomarker for pancreatic cancer. Abstract : Using proteomic analysis, we identified that ZIP4 was the most upregulated exosomal protein in PC‐1.0 cells. In vitro and in vivo experiments showed that exosomal ZIP4 could promote pancreatic cancer growth. Validation with clinical samples proved that exosomal ZIP4 could be a novel diagnostic biomarker for pancreatic cancer.